2021
DOI: 10.1055/s-0041-1722984
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tinnitus Sound Therapy Determined Using Subjective Measurements

Abstract: Background Sound therapy is generally considered as an effective method for relieving tinnitus. There have been various reports on the effects of tinnitus interventions involving sound therapy as a component; however, there have been only a small number of reports on the effects of sound therapy itself on tinnitus. Purpose The aim of the study is to elucidate whether sound therapy significantly improves tinnitus as determined by subjective measurements. Research Design Prospective study inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Second, the daily treatment time for patients was relatively short; a longer daily sound therapy duration might enhance the potential for improving tinnitus relief 9 . There is evidence that continuous sound therapy for longer periods, such as 3 h per day for > 6 months, could yield better results 8 . Third, the trial was conducted in a single center, which may limit the generalisability and stability of the findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the daily treatment time for patients was relatively short; a longer daily sound therapy duration might enhance the potential for improving tinnitus relief 9 . There is evidence that continuous sound therapy for longer periods, such as 3 h per day for > 6 months, could yield better results 8 . Third, the trial was conducted in a single center, which may limit the generalisability and stability of the findings.…”
Section: Discussionmentioning
confidence: 99%
“…Sound therapy, assessed through subjective evaluations, has demonstrated effectiveness in tinnitus management. The efficacy of sound therapy improves with the duration of daily treatment; it can be effective as a standalone method without additional counseling 8 , 9 . Vernon 10 demonstrated that tinnitus masking, a standard monotone therapy, involves using external noise to distract the patient's attention and reduce the contrast between the tinnitus signal and background activity within the auditory system.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, 5 of 15 participants with chronic tinnitus who received sound therapy reported significant relief from tinnitus [8]. Sound therapy does not appear to be effective for all patients with chronic tinnitus; however, many studies have reported significant reductions in tinnitus or habituation to tinnitus in some participants who have undergone sound therapy [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Whether rehabilitation combining sound and electrical stimulation is more effective than traditional sound therapy remains unclear. Studies on sound therapy alone have also reported significant tinnitus relief in 30-50% of participants when assessing individualized tinnitus relief [9,11]. However, studies on sound therapy alone and those combining sound and electrical stimulation are not directly comparable because of differences in participant characteristics, rehabilitation duration, and assessment methods.…”
Section: Introductionmentioning
confidence: 99%